Хоёр ёсны сургаалаар төрөө засаж ирсэн уламжлал - Ш.Чоймаа (Acta Mongolica, 2008)
In this article the Doctrine of Two Principles is traced from the time when, according to historical legends, the universe was created and its first king Mahasamadi appeared. Among the Mongolians the Doctrine of Two Principles started to spread out since the time when Sakya pandita Gungaajaltsan (1182-1251) was invited to Mongolia by Godan Khan (1205-1251), who was dedicated to the Buddhist religion. As mentioned in "The Chronicles of the Cakya Genealogy", compiled in 1629 by Agvangungaa Sodnam, Godan Khan ordered that he would support with the state doctrine while Sakya pandita should deal with the religious teachings, then the Shagjamuna's religion would spread throughout the land till the outer ocean. In this saying the Doctrine of Two Principles is clearly meant. During the Yuan Dynasty Khubilai Khan kept the doctrine quite strictly in his state policy. It can be clarified from his edit to the Tibetan monks and the mass, issued in 1264, the period earlier than "White Chronicle" was compiled. This document asserts how Khubilai Khan comprehended the Two Principles. The content of the "White Chronicle" is reviewed in this article shortly since the chronicle presents the basic legislative document to conduct both the civil and religious affairs to satisfy the mass in joyfulness of body, speech and mind.